2010
DOI: 10.1007/s12199-010-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intervention for low back pain in female caregivers in nursing homes: a pilot trial based on multicenter randomization

Abstract: Objectives Although the importance of stretching exercise for pain-relieving and patient education is well documented for chronic lumbago patients, it is uncertain how effective on-the-job training (OJT) is for female caregivers in nursing homes. In the present pilot trial based on multicenter randomization, we evaluated the intervention effect of a lecture and stretching exercise on caregivers in nursing homes. Methods Eighty-eight female caregivers (four nursing homes) volunteered to participate in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Factors that showed significant association with LBP among nursing staff in the multivariate analysis were age, nationality, menstrual disorders and stress level at work. Kamioka et al [8] found that there is no significant differences were seen for any outcome measurements.…”
Section: Results Of Reviewed Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Factors that showed significant association with LBP among nursing staff in the multivariate analysis were age, nationality, menstrual disorders and stress level at work. Kamioka et al [8] found that there is no significant differences were seen for any outcome measurements.…”
Section: Results Of Reviewed Studiesmentioning
confidence: 91%
“…The presence of LBP is significant, as most nurses will have a persistent pain throughout their lifetime, proven by Maul et.al. [18], which may contribute to early retirement (8).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 provides a brief summary of the six articles. The types of intervention were as follows: multidimensional method (Miyamoto et al, 1998 andSvensson et al, 2008); transfer technique and stress management (Jensen et al, 2006); lumbar support (Roelofs et al, 2007); stretching exercise (Kamioka et al, 2011); and cognitive behavioral theory (Menzel et al, 2006). In the main outcome measurement (for pain-relieving), it was only lumbar support that was statistically significantly effective (Svensson et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…For lumbar support, it cost 50-70 euros per one unit (Roelofs et al, 2007). For stretching exercise, it cost 2,000 dollars as an overall training expense (Kamioka et al, 2011). And, for cognitive behavioral intervention, the compensation to a participant of one hour was shown to be 17 dollars (Menzel et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation